Pulmonary hypertension in polymyositis. Issue 12 (December 2015) - Wang, Han; Liu, Tao; Cai, Ying-ying; Luo, Lian; Wang, Meng; Yang, Mengmeng; Cai, Lin
Abstract Pulmonary hypertension (PH) is relatively common in connective tissue diseases. However, few studies have focused on the pulmonary hypertension (PH) associated with polymyositis (PM). Our aim is to investigate the prevalence of PH and determine the associated factors for PH in patients with PM. Multicenter study of 61 patients with PM underwent evaluation including general information, physical examination, laboratory indictors, thoracic high-resolution CT (HRCT) imaging, and transthoracic echocardiography (TTE). TTE was performed to estimate the pulmonary arterial pressure. PH was defined as resting systolic pulmonary artery pressure (sPAP) ≥40 mmHg. PH was identified in ten patients (16.39 %) who had few cardiopulmonary symptoms. PM patients with PH had higher prevalence of interstitial lung disease (ILD) and pericardial effusion (PE) compared with patients without PH (18 vs. 11.5 %, p  = 0.005; 11.5 vs. 9.8 %, p  = 0.004; respectively). After controlling for age, gender, and potential factors, ILD and PE were independently associated with PH in patients with PM in multivariate analysis (OR = 8.193, 95 % CI 1.241–54.084, p  = 0.029; OR = 8.265, 95 % CI 1.298–52.084, p  = 0.025; respectively). Depending on TTE, the possible prevalence of PH was 16.39 % in patients with PM. Both ILD and PE may contribute to the development of PH in PM.